The Bank Guarantee as an Instrument for Improving the Liquidity of Enterprises under the Conditions of the COVID-19 Pandemic - Kowalik, Małgorzata (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2022)
Objective: The article analyses the risk accompanying commercial transactions, which is growing and needs to be limited as it worsens financial liquidity in enterprises. The article identifies and determines the causes of this growing risk, and indicates the important role which bank guarantees play as a hedge against this risk. Bank guarantees primarily allow companies to maintain liquidity in a turbulent environment, one fraught with increasing risks characterising commercial transactions between counterparties. Currently, the consequences of the COVID-19 pandemic that European and global economies are facing have significantly destabilised the economic situation. These consequences are taken into account in the article.Research Design & Methods: The research methods used to develop the article included a study of the subject literature and analysis of reports and research results on the situation that enterprises in Poland and the rest of Europe are facing.Findings: The results obtained confirm the hypothesis that bank guarantees constitute an important instrument for improving the financial liquidity of enterprises, especially in the conditions prevailing as a result of the COVID-19 pandemic.Implications / Recommendations: The conclusions drawn indicated that bank guarantees, as well as other special programmes designed to support the activities of enterprises, can help reduce the risk of conducting business activity, particularly the risk of losing financial liquidity.Contribution: The article adds to the analysis and knowledge base on ways of reducing the risk of losing financial liquidity.